Analisis Faktor-faktor Yang Mempengaruhi Mutu Beton Ready Mix - Yola Andara Pratami Suri; Vera Agustriana Noorhidana; Masdar Helmi; Muhammad Isneini; Endro Prasetyo Wahono (Teras Jurnal: Jurnal Teknik Sipil)
Abstrak